Contemporary Challenges in Combating Economic Crime: A Case Study of Ukraine - Yuliia Shvets; Yurii Orlov; Yevhen Shaptala; Vasyl Kikinchuk; Maksym Kuterha; Maksym Korniienko; Yevhen Sup (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2026)
This study identifies and analyzes contemporary challenges in combating economic crime in modern states, using Ukraine as a case study. Combining doctrinal legal analysis with descriptive secondary data, it draws on statutory and international-convention reviews, as well as institutional reports, including January–September 2024 data from the State Financial Monitoring Service of Ukraine, to examine the structural, operational, and legal dimensions of economic-crime enforcement. The analysis is descriptive and interpretive rather than causal. Over the nine-month period, more than 1.3 million financial transactions were reported for monitoring, with roughly one in five flagged for suspected money laundering, corruption, or terrorism financing; yet only a small share progressed to referral, prosecution, or confiscation. The enforcement chain narrows most sharply not at the generation of financial intelligence but at its conversion into investigations and resolved cases, an attrition that coincides with weak inter-agency coordination, limited adoption of advanced financial analytics, fragmented legal frameworks, and constrained cross-border data-sharing. A comparison with the more highly rated regimes of Singapore and Estonia, drawn from their mutual-evaluation reports, locates the same downstream bottleneck and clarifies where Ukraine's framework falls short. The study contributes a descriptive map of the interplay between institutional capacity and cross-border legal constraints in economic-crime enforcement. It proposes operational measures, including binding inter-agency service-level agreements, real-time data-exchange platforms, certified investigator training, and updated mutual legal assistance treaties enabling early-stage asset tracing, to help move enforcement from formal compliance toward measurable outcomes.